Les antécédents de la relation acheteur-vendeur : le rôle médiateur du partage de la connaissance - Kohail , younes (Revue Internationale des Sciences de Gestion, 2020)
This study aims to test the effects of buyer-seller relationship antecedents and test the mediating role of knowledge sharing. A quantitative study based on a sample of 100 marketing managers in small medium companies. Data were analyzed using the PLS Structural equation modeling. Findings show that Knowledge sharing, contract specification level and opportunistic behavior have a positive effect on buyer-seller relationship; however, power asymmetry has a negative effect. In addition, contract specification level, Dysfunctional conflict, opportunistic behavior were found to have a positive effect on knowledge sharing, however, power asymmetry has a negative effect.